2015
DOI: 10.1037/emo0000011
|View full text |Cite
|
Sign up to set email alerts
|

Launching reappraisal: It’s less common than you might think.

Abstract: Cognitive reappraisal is thought to be ubiquitous. However, no studies have quantified how frequently people reappraise (vs. letting their emotional response go unregulated). To address this issue, the authors created a laboratory decision context in which participants watched a series of negatively valenced images, and in each case had the option of electing to reappraise to decrease negative affect. Given the many benefits and few costs associated with reappraisal, we expected that most images would be reapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 12 publications
7
71
1
1
Order By: Relevance
“…Recent work finds that, when possible, participants report using multiple ER strategies in response to brief stressors (e.g., Aldao & Nolen-Hoeksema, 2013;Heiy & Cheavens, 2014). Our findings mirror recent research indicating low endorsement of reappraisal even at low emotional intensities (Suri, Whittaker, & Gross, 2014), presumably due to hidden costs (such as the high level of required effort) associated with this strategy.…”
Section: Discussionsupporting
confidence: 88%
“…Recent work finds that, when possible, participants report using multiple ER strategies in response to brief stressors (e.g., Aldao & Nolen-Hoeksema, 2013;Heiy & Cheavens, 2014). Our findings mirror recent research indicating low endorsement of reappraisal even at low emotional intensities (Suri, Whittaker, & Gross, 2014), presumably due to hidden costs (such as the high level of required effort) associated with this strategy.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, perspective taking may be particularly challenging in romantic conflict situations characterized by strong feelings about unmet needs. In an experimental study, Suri, Whittaker, and Gross () found that proactive reappraisal of negative experiences to reformulate their meaning is more difficult than previously thought. Other narrative research on emerging adults' self‐defining memories found that the ability to gain insight into conflict situations with peers and family is uncommon (McLean & Thorne, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it seems that reappraisal is maladaptive when stressors can be controlled (i.e., when the situation can be modified by means of active coping), therefore calling into question the "unconditional" link between reappraisal and resilience. Perhaps as a consequence of these moderator effects of both intensity and controllability of the stressor, individuals surprisingly rarely chose cognitive reappraisal as an emotionregulation strategy when they were free to do so (Suri et al 2014).…”
Section: Boris Egloffmentioning
confidence: 99%